Novel co-precipitated oxygen carriers for chemical looping combustion of gaseous fuel - Ekpe, Ngozi Chinwe (2017)
Carbon Capture and Storage (CCS) is one option to meet the increasing energy demand as well as reduce net CO2 emissions to the atmosphere. Chemical Looping Combustion (CLC) is a promising CCS technology proposed to meet the challenge of mitigating the carbon dioxide (CO2) emissions. CLC process can be based on interconnected fluidized beds, consisting of air reactor, fuel reactor and oxygen carrier (OC) which undergoes redox reactions while it circulates between the reactors. The main products are CO2 and water, thus eliminating the need of an additional energy intensive CO2 separation.